JC virus infects the enteric glia of patients with chronic idiopathic intestinal pseudo-obstruction. Issue 1 (1st July 2008) - Selgrad, M; De Giorgio, R; Fini, L; Cogliandro, R F; Williams, S; Stanghellini, V; Barbara, G; Tonini, M; Corinaldesi, R; Genta, R M; Domiati-Saad, R; Meyer, R; et al.
Abstract : Background and aim: Chronic idiopathic intestinal pseudo-obstruction (CIIP) is characterised by severe impairment of intestinal propulsive motility that mimics bowel obstruction. JC virus (JCV) is a polyomavirus that can infect brain glial cells causing a fatal disease, but may also be found throughout the normal gastrointestinal tract. The hypothesis that JCV infects the myenteric plexuses of patients with CIIP was tested. Methods: 10 patients with CIIP and 61 normal specimens (30 ascending colon and 31 ileum) from patients with uncomplicated colon cancer were studied. DNA was extracted from the myenteric plexuses, and JCV T antigen (TAg) DNA and the viral regulatory region were detected by PCR and sequencing. Immunohistochemistry was performed to detect JCV viral protein expression, neuronal and glial markers. Fluorescence in situ hybridisation was performed for cellular localisation of the JCV infection. Results: Clinical studies demonstrated neurogenic impairment, and pathological analyses showed neuropathy in each patient with CIIP. JCV TAg DNA was found in the myenteric plexuses of 8/10 (80%) of the patients with CIIP and 3/31 (9.7%) of the control patients (p<0.001). All samples were JCV Mad-1 strains. Seven of the 10 CIIP specimens expressed both JCV TAg and the JCV viral protein VP1, while none of the controls expressed either. JCV infection co-localised with glial fibrillary acidic protein expression, a marker of enteric glial cells. Conclusion: JCV infection occurs in the myenteric plexuses of patients with CIIP. The JCV localisation in enteroglial cells suggests a possible pathological role for this virus in enteric neuropathy.